An Atypical Case of Bullous Systemic Lupus Erythematosus in a 16‐Year‐Old Boy. Issue 6 (21st July 2014) - Christodoulou, George; Powell, Mathieu; Nguyen, Van‐Hung; Watters, Kevin; Jafarian, Fatemeh
Abstract Bullous systemic lupus erythematosus (BSLE) is a rare autoimmune subepidermal blistering disease with a female predominance characterized as an acute vesicobullous eruption in patients with systemic lupus erythematosus (SLE). Here we report a case of BSLE in a 16‐year‐old boy that does not adhere to the criteria originally established and suggest a new outlook on this condition.